Analisis Faktor-Faktor Perambahan Hutan pada Kawasan Resort Konservasi Wilayah II Taman Wisata Alam (TWA) Ruteng di Desa Ngkiong Dora Kecamatan Lamba Leda Timur, Kabupaten Manggarai Timur, Provinsi Nusa Tenggara Timur - Berta Adelina Ria; Ludji Michael Riwu Kaho; Fadlan Pramatana (Wana Lestari, 2023)
This study aims to determine the factors that cause forest encroachment in TWA Rutengside Ngkiong Dora Village.The research method used is descriptive qualitative analysis and percentage tabulation.sampling technique used purposive sampling. The data collection was done through structured interviews, in-depth interviews, field observations, documentation and literature studies. The results of the study concluded that forest destruction in TWA Rutengside Ngkiong Dora Village was caused by 3 (three) factors, namely; economic factors, community socio-cultural factors, and the limited number of forest security supervisors.Economic factors refer to the area of land owned by the community which is categorized as "small" with a wide range (> 1ha) so that it affects the level of community income in meeting the needs of life. The income level of the community ranges from RP.201.00- RP.400,000 per month in the low income category. While the socio-cultural factors of the community such as the level of public education are still low, where the highest education level is elementary school (92.40%). The age level of the squatters was mostly in the old productive category (60.76%). The livelihoods of squatters are 100% as farmers with the number of dependents of squatters in each household ranging from 4-5 people with a percentage of 67.08%. While the level of public awareness is still very low, as well as the influence of local culture in land management in Ngkiong Dora Village. Limited number of quality, as well as quantity of forest security supervisory staff in managing Ruteng TWA.